Pengaruh Desain Interior pada Kenyamanan Pengunjung di FDC Dental Clinic - Laksitarini, Niken; Nugroho, Ardianto; Rizki, Salsabila Zashika; Perkasa, Ciputra Tegar (Program Studi Desain Interior Unikom, 2024)
FDC Dental Clinic has 24 branches spread across Jakarta, Bogor, Depok, Tangerang, Bekasi, Bandung, Surabaya and Yogyakarta. FDC Dental Clinic is a dental clinic that has a thematic concept with the hope that visitors will feel comfortable during the examination process and when queuing in the waiting room. Convenience at the dental clinic is one of the most important things that directly affects the perception of visitors, in the end if the visitor's perception of the clinic is negative, it will cause reluctance to visit and have their teeth examined. color, texture, lay out furniture and lighting. The purpose of this study was to find out how external factors found in the interior can affect psychological (internal factors). The benefit for visitors, especially children, is to be able to reduce the feeling of discomfort when they are in the dental clinic. The method used in this study is a descriptive qualitative approach with data collection in the form of field observations, interviews and questionnaires distributed to visitors. The results and conclusions drawn from this study will include the extent to which interior design influences the comfort of dental clinic visitors, especially children.Keywords: convenience, dental clinic, interior